Strategic finance choices: embracing the relevance of equity financing over debt financing - Mohamad Yunus, Fauziah; Abu Hassan, Mohamad Hanif; Wahab, Muhammad Zarunnaim (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2024)
This study examines the challenges inherent in debt financing and proposes equity financing as a strategic solution. Issues under debt financing, including financial strain, default risk, substantial interest costs, and restrictive covenants, are analysed. Equity financing is presented as a remedy, allowing businesses to raise capital without incurring debt, reducing financial strain, and eliminating interest costs. The study emphasises equity financing's capacity to enhance financial flexibility, share risks through ownership, foster strategic partnerships, and provide resilience in economic downturns. It concludes by underscoring the need for businesses to align their financial structures with specific needs, acknowledging the trade-offs between debt and equity financing. This exploration invites future research into industry-specific analyses, macroeconomic influences, and hybrid financing models to refine financial strategies. Overall, the study advocates for a nuanced understanding of financing mechanisms to foster sustainable and resilient business practices.